A Plant Characterization Unit for Closed Life Support: Hardware and Control Design for Atmospheric Systems - Pannico, Antonio; Cimini, Gionata; Quadri, Claudia; Paradiso, Roberta; Bucchieri, Lorenzo; Rouphael, Youssef; De Pascale, Stefania (Frontiers in Astronomy and Space Sciences, 2022)
Growth chambers are critical to the characterization of higher plant performance within BLSSs for long term crewed missions in Space. The Plant Characterization Unit (PCU) is a 2.16 m3 environmentally controlled sealed chamber, realized in 2019 at the Laboratory of Crop research for Space of the University of Naples (Italy), within the European Space Agency Programme MELiSSA. The PCU enables terrestrial investigations of BLSS higher plant compartments that produce food, water, and oxygen for the crew. It accommodates two separate sub-systems, an atmospheric module and a hydroponic module. Such systems regulate autonomously temperature, relative humidity, light intensity and spectral composition, atmosphere gas composition, and air flow and pressure, as well as the composition, the temperature and the flow of the nutrient solution. This method paper describes the following phases of realization: 1) the definition of plant requirements; 2) the design of the two modules; 3) the development of the control system for the atmospheric sub-system.